1981
DOI: 10.1007/bf01890250
|View full text |Cite
|
Sign up to set email alerts
|

Intramural pseudodiverticulosis of the esophagus: Report of seven cases and literature review

Abstract: Seven cases of esophageal intramural pseudodiverticulosis (EIPD) are presented and compared with 46 cases previously reported. EIPD is mainly a disease of older age with a 3:2 predominance of male patients. The radiologic appearance of EIPD shows great variation in localization and severity of visible changes. Radiologic examination is far more sensitive than endoscopy in diagnosing EIPD. The most effective therapy for EIPD is dilatation of strictures, leading to amelioration or disappearance of symptoms in ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
72
1

Year Published

1991
1991
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(74 citation statements)
references
References 29 publications
1
72
1
Order By: Relevance
“…EIPs are distributed diffusely in 60% of patients and segmentally in 40% (upper 14%, middle 14%, and lower 12%) of patients. 8,11 In our case, pseudodiverticula were diffusely present through the entire esophagus. An esophageal stricture is observed in 76-90% of patients, which are most common in the upper esophagus, followed by the lower esophagus and middle esophagus.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…EIPs are distributed diffusely in 60% of patients and segmentally in 40% (upper 14%, middle 14%, and lower 12%) of patients. 8,11 In our case, pseudodiverticula were diffusely present through the entire esophagus. An esophageal stricture is observed in 76-90% of patients, which are most common in the upper esophagus, followed by the lower esophagus and middle esophagus.…”
Section: Discussionmentioning
confidence: 48%
“…8 EIP shows bimodal peak incidence in teens 9,10 and in the fifties and sixties. 11,12 Patients who have a coexisting disease such as diabetes mellitus, esophageal candidiasis, reflux esophagitis, chronic alcohol abuse, and corrosive acid injury have a higher risk to develop EIP. 8,13 EIP is often associated with benign esophageal disease, but there are several reports where EIP was associated with esophageal cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The exact pathogenesis is unknown, however, theories by Wightman, Lupovitch and Murney include duct occlusion by metaplasia, inflammation or elevated intraluminal pressure respectively [5]. It can be segmental in 40% (upper 14%, middle 14%, and lower 12%) or diffuse in 60% [6]. The role of Candida has been reported controversial whether it is a cause or found incidentally.…”
Section: Discussionmentioning
confidence: 99%
“…Necropsy studies, however, have shown pseudodiverticula to be dilated pre-existing excretOesophageal intramural pseudodiverticulosis ory ducts of the submucous glands. 44 46 This suggests that intramural pseudodiverticulosis of the oesophagus may represent yet another complication of reflux oesophagitis. Intramural pseudodiverticulosis of the oesophagus seems to have no clinical importance as such, but is an indication that " something is amiss" in the oesophagus.…”
Section: Discussionmentioning
confidence: 99%